2015
DOI: 10.1111/iar.12116
|View full text |Cite
|
Sign up to set email alerts
|

The Godzilla Megamullion, the largest oceanic core complex on the earth: a historical review

Abstract: The Godzilla Megamullion is the largest known oceanic core complex (OCC) on the Earth, located in the Parece Vela Basin in the Philippine Sea. In this article, the history of Godzilla Megamullion study is reviewed for the first time, dividing it into three major phases: (i) the early studies done before Japan's extended continental shelf survey program; (ii) the studies during Japan's extended continental shelf survey program that discovered the OCC; and (iii) the studies by the post-discovery cruises. The ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…). A total of 67 samples were obtained from this dredge site during cruise KH07‐02 (Leg 4) aboard the R/V Hakuho‐maru (Ohara ). Fifty‐seven gabbroic rocks of the 67 samples consist mainly of Fe–Ti oxide gabbro with minor gabbro, and are generally hydrated, deformed, and Mn‐coated.…”
Section: Sample Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…). A total of 67 samples were obtained from this dredge site during cruise KH07‐02 (Leg 4) aboard the R/V Hakuho‐maru (Ohara ). Fifty‐seven gabbroic rocks of the 67 samples consist mainly of Fe–Ti oxide gabbro with minor gabbro, and are generally hydrated, deformed, and Mn‐coated.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…; Ohara et al . , ; Ohara ). Based on zircon U–Pb dating of Godzilla gabbroic and leucocratic rocks, Tani et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…トランスフォーム断層帯に露出する"abyssal peridotite" (Dick, 1989;Warren, 2016)や,マ グマ供給率が低い低速拡大軸で発生する"oceanic core complex"または"megamullion" (Dick et al, 2008;Ohara, 2015 (Hirano et al, 2006) 。溶岩の組成は,プレート 直下のアセノスフェアの情報を多く残している可 能性が高い。さらに,噴出した溶岩は,海洋地殻 からマントルにかけてそれぞれ捕獲岩または捕獲 結晶を含有している (Hirano et al, 2004(Hirano et al, , 2006Harigane et al, 2011;Yamamoto et al, , 2014 1. トンガ海溝海側斜面 (Hirano et al, 2008) 2. チリ海溝海側斜面 (Hirano et al, 2013) 3. 北 米 Basin and Range(Valentine and 4. グ リ ー ン ラ ン ド 南 方 海 域 (Uenzelmann-Neben et al, 2012) 5. コスタリカ付加体 (Buchs et al, 2013) 6. ジャワ海溝海側斜面・クリスマス島(Taneja et al, 2015) 7. フレンチポリネシア周辺海域 (Hirano et al, 2016) (Clouard and Bonneville, 2001) (Wang et al, 2006;Yoshino et al, 2006;Mierdel et al, 2007;Gaillard et al, 2008;Kawakatsu et al, 2009;Rychert and Shearer, 2009;Conrad et al, 2011;Sakamaki et al, 2013;Sifré et al, 2014;Beghein et al, (Hirano et al, 2001(Hirano et al, , 2004(Hirano et al, , 2006 Hirano et al (2006) 中の Fig. S2 を参照されたい. Fig.…”
unclassified
“…This virtual special issue is derived from the successful workshop, summarizing the current understanding of the OCC. Ohara () reviewed the history of the Godzilla Megamullion studies, providing a sound background information for studying the OCC to the ocean lithosphere communities. Sanfilippo et al () reported the trace element compositions of the clinopyroxene and plagioclase of the Godzilla troctolites, discussing the importance of melt‐mantle interaction of the composition of the lower oceanic crust, and its importance for the evolution of Mid‐Ocean Ridge Basalt.…”
mentioning
confidence: 99%